196k views
0 votes
Find the average rate of change of f(x) = 4x^2 – 3 on theinterval [1, a]

User Wituz
by
4.0k points

1 Answer

6 votes

Average rate of change is given by the equation


(f(x2)-f(x1))/(x2-x1)

x1=1

x2=a

Find f(1) and f(a)


\begin{gathered} f(1)=4\cdot(1^2)-3=4-3=1 \\ f(a)=4\cdot a^2-3=4a^2-3 \end{gathered}

Find the average rate of change


((4a^2-3)-1)/(a-1)=(4a^2-4)/(a-1)

Factor


(4a^2-4)/(a-1)=(4\cdot(a-1)\cdot(a+1))/(a-1)=4\cdot(a+1)=4a+4

The average rate of change is 4a + 4 on the interval [1,a]

User Lucianosousa
by
5.3k points